Square peg, round hole: Why the EU can't fix identity politics - Turkuler Isiksel (London School of Economics and Political Science (LSE), European Institute, 2018)
European societies are once more in the grip of the kind of identity politics that decades of carefully constructed economic relationships were supposed to obviate. This paper argues that if the EU is ill-equipped to meet this challenge, it is not so much because of its bias in favor of deregulation, as leftist critics contend, but because the only tools at its disposal for doing so are of an economic nature. For this reason, it is unclear whether an alternative, social democratic model of supranationalism would do much resolve the discontents of identity politics. In fact, since such a project would require vesting the EU with even greater power and fiscal capacity, it is likely to have the opposite effect, at least in the near term.
Keywords: 330